A secure and cloud-based patient management system using attribute-based encryption algorithm - Kalarani, Senthilkumar; Shobana, Mahalingam; Shankari, Edamakanti Uma; Praveena, Bolly Joshi; Shanthi, Subramaniam; Ramadevi, Rathinasabapathy; Sandiri, Rajendar (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Using attribute-based encryption (ABE), cloud-based patient management systems may be made more secure and efficient. The goal is to provide a scalable encryption infrastructure with dynamic attribute handling and context-aware access control for safe data access. Encryption procedures should directly comply with regulatory criteria to secure healthcare data and ensure data privacy and integrity. Secure attribute issuance and revocation are achieved using advanced key management and real-time auditing and monitoring to identify and react to unauthorised access. To help healthcare providers handle data, user-centric security measures including extensive training and adaptive security procedures are used. The encryption system is implemented and maintained using cost-effective cloud and open-source methodologies to ensure seamless integration and operational effectiveness in healthcare contexts. First, secure patient management system dataset results reveal ABE algorithm encryption. The encrypted values are 8F5D6A..., 7C4A3B..., 6E3B2C..., 9D8A7B..., 5E4D3C.... in the second instance, derived from role-based access control of ABE. The patients are 25-60 years old, have medical codes 101-105, 201-205, and 301-305. For roles from different fields, attribute code is 401-406, level code is 501-505.